2020
DOI: 10.1007/s13555-020-00357-z
|View full text |Cite
|
Sign up to set email alerts
|

Local Management of Anogenital Warts in Non-Immunocompromised Adults: A Network Meta-Analysis of Randomized Controlled Trials

Abstract: Introduction:No hierarchy of first-line treatments for anogenital warts (AGWs) is provided in international guidelines. This study aimed to determine the efficacy of topical treatments and ablative procedures for the management of AGWs. Methods: Twelve electronic databases were systematically searched from inception to August 2018. All randomized controlled trials (RCTs) comparing immunocompetent adults with AGWs who received at least 1 provideradministered or patient-administered treatment in at least 1 paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 89 publications
0
23
0
Order By: Relevance
“…The efficacy of NZCS has been described previously in five studies [ 8 11 , 17 ]. The first of these, published in 2015 by Cusini et al [ 17 ] showed that NZCS has an 87% efficacy in 30 patients after one to four applications [ 17 ].The second study, published by Rozas-Munoz et al in 2019 [ 10 ], involved 15 patients and reported an efficacy of 88.3% and no recurrence in the 3-month follow-up. The third study, by Ciccarese et al [ 8 ], also published in 2019, is one of the most interesting due to the number of patients treated (100), the number of AGW treated (418) and the length of follow-up (6 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of NZCS has been described previously in five studies [ 8 11 , 17 ]. The first of these, published in 2015 by Cusini et al [ 17 ] showed that NZCS has an 87% efficacy in 30 patients after one to four applications [ 17 ].The second study, published by Rozas-Munoz et al in 2019 [ 10 ], involved 15 patients and reported an efficacy of 88.3% and no recurrence in the 3-month follow-up. The third study, by Ciccarese et al [ 8 ], also published in 2019, is one of the most interesting due to the number of patients treated (100), the number of AGW treated (418) and the length of follow-up (6 months).…”
Section: Discussionmentioning
confidence: 99%
“…In their recent meta-analyses on the effectiveness of treatments for AGW, Barton et al [ 15 ] conclude that laser CO 2 seems to be the most effective method but also that patient preference tends towards nonablative methods. Bertolotti et al [ 16 , 17 ] indicate electrosurgery and 0.5% podophyllotoxin as the most effective methods and recommend an randomised controlled trial on the combined therapies.…”
Section: Introductionmentioning
confidence: 99%
“…TLR7/8 natural agonists imiquimod and resiquimod have been used against basal cell carcinoma [34,35], melanoma, and other skin neoplasms [36] as well as against common warts [37,38]. Local imiquimod has also been used in combination with radiotherapy for breast cancer in the clinic [39].…”
Section: Intratumoral Delivery Of Pathogen-associated Moleculesmentioning
confidence: 99%
“…Pontini et al evaluated AGW recurrence at 1 and 3 months [ 1 ]. However, given that AGW recurrence has been shown to be fairly common 6 months after treatment [ 9 11 ], they should also have done so at 6 and 12 months. Lastly, it should be noted that while ablative therapies (surgery, electrosurgery, CO 2 laser) are more effective than patient-administered treatments in the short term [ 4 , 9 ], the latter may be superior in the long term due to their immunomodulatory effects.…”
Section: Digital Featuresmentioning
confidence: 99%